The Effect of Educational Facilities and Infrastructure Management and Teacher Professionalism on Learning Quality in Public Elementary Schools in Suak Tapeh District, Banyuasin - Sumiaryah; Bukman Lian; Muhammad Fahmi (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aimed to analyze the effect of educational facilities and infrastructure management and teacher professionalism on learning quality at public elementary schools in Suak Tapeh District, Banyuasin Regency. The study employed a quantitative approach with an ex post facto design. The population consisted of 161 teachers, and 100 teachers were selected through proportional probability sampling. Data were collected using Likert-scale questionnaires and documentation. The instruments were valid and reliable, with Cronbach's alpha coefficients of 0.902 for facilities and infrastructure management, 0.906 for teacher professionalism, and 0.891 for learning quality. Data were analyzed using descriptive statistics, prerequisite tests, simple linear regression, and multiple linear regression with SPSS version 26. Facilities and infrastructure management had a positive and significant effect on learning quality (B = 0.495; t = 4.984; p < 0.001; R² = 20.2%). Teacher professionalism also had a positive and significant effect on learning quality (B = 0.619; t = 7.322; p < 0.001; R² = 35.4%). Simultaneously, both predictors had a positive and significant effect on learning quality (F = 31.751; p < 0.001; R² = 39.6%), with the equation Y = 0.952 + 0.253X₁ + 0.512X₂. These findings contribute empirical evidence that learning quality improves when schools manage educational facilities effectively and sustain teachers' professional development.